Multifunctional flame-retardant anti-dripping copolyester as well as preparation method and application thereof

By introducing specific structural units into the polyester, a multifunctional flame-retardant and droplet-resistant copolyester was developed, which solved the problems of flammability and insufficient performance of polyester materials in fire, and achieved excellent comprehensive performance of flame-retardant, antibacterial, ultraviolet and high-performance strength.

CN119505204APending Publication Date: 2025-02-25SICHUAN UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202311060993.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing polyester materials are flammable in fires and produce a large number of ignition-carrying droplets, threatening life and property safety, while at the same time lacking in antibacterial, UV resistance and high performance strength.

Method used

Develop a multifunctional flame retardant and droplet copolyester to achieve comprehensive performance of flame retardant, antibacterial, UV resistance and high performance strength by introducing specific structural units into the polyester. The copolyester can promote the carbonization reaction of the polyester at high temperatures, form a stable and dense carbon layer, and significantly improve the flame retardant performance.

Benefits of technology

The copolyester is produced without droplets during combustion, has excellent flame retardant properties and droplet resistance, and can self-catalyze and depolymerize without an external catalyst to promote resource recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505204A_ABST
    Figure CN119505204A_ABST
Patent Text Reader

Abstract

The multifunctional flame-retardant anti-dripping copolyester is composed of structural units represented by I, II, III or I, II, III and IV, when the structural unit [III] is represented by a formula A-W, the number of the structural units [III] is 0.1-99% of that of the structural units [I], and the number of the structural units [IV] is 0.1-99% of that of the structural units [I]; and when the structural unit [III] is of the structure shown in the formula X, the number of the structural units [III] is 0.1-0.99% of the number of the structural units [I], and the number of the structural units [IV] is 0.1-99% of the number of the structural units [I]. The invention also discloses a preparation method and application of the compound. The copolyester disclosed by the invention not only has excellent flame retardance, molten drop resistance, smoke suppression property and mechanical strength, but also has good functions of ultraviolet resistance, bacteria resistance, cationic dyeability and the like, has a good application prospect, and is beneficial to development of high-performance and high-added-value differential polyester products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of copolyester materials and their preparation and application. Specifically, the present invention relates to a flame-retardant and anti-melting-drip copolyester with multiple functions such as anti-ultraviolet, antibacterial, cationic dyeable, and self-catalytic recycling, and a preparation method and application thereof. Background Art

[0002] Thermoplastic polyester materials, such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT) or polybutylene succinate (PBS), are used as synthetic fibers, films, bottling materials and engineering plastics due to their excellent thermal stability, mechanical properties, conformality, corrosion resistance, low gas permeability and other advantages. In 2021, the output of polyester materials in my country will reach more than 50 million tons, with a very large production capacity and consumer market. However, polyester also faces very serious fire safety issues. Not only is it easy to burn, but also because of the low melt viscosity and melt strength of polyester at high temperatures and poor charring ability, a large amount of flammable droplets will be produced during combustion, threatening life and property safety. In recent years, fire accidents have occurred frequently, and the inherent flammability of polymer materials can easily cause fires, resulting in irreparable loss of life and property. At the same time, in special fields such as fire suits, combat uniforms, military tents / tarpaulins, and textiles for public places, in addition to the flame retardant requirements for polyester materials, there is also an urgent need for its antibacterial, UV resistance, high performance strength and other properties. Therefore, polyester materials that combine flame retardancy, anti-melting and functionalization are a major demand for national economic and social development.

[0003] At present, the flame retardant functionalization of polyester materials is mainly achieved through fabric finishing, physical blending, and chemical copolymerization. Fabric finishing is a simple process with relatively low cost, but it often has problems such as non-persistent functions, poor water resistance, poor wear resistance, and poor hand feel. The physical blending method is prone to cause serious damage to the mechanical properties and spinnability of polyester due to the easy migration and poor dispersion of various additives in the polyester substrate. There are very few research reports on flame retardancy and functionalization through chemical copolymerization, but this method can retain the good spinnability and mechanical properties of polyester itself to a large extent.

[0004] In addition, it is particularly worth mentioning that with the widespread use of polyester materials, a large amount of polyester materials are discarded after use every year, and most of the waste polyester materials (such as waste polyester fiber textiles) are incinerated and landfilled, which not only wastes a lot of natural resources, but also causes environmental pollution. At the same time, functional and flame-retardant polyester materials are added with corresponding functional additives or flame retardants. For example, although the flame retardant can achieve flame retardancy at high temperature (or when the polymer burns) by absorbing heat, inhibiting free radical combustion chain reactions or generating non-flammable gases, it will also bring many problems and difficulties to the recycling of polyester materials. For example, these flame retardant reactions will occur during the chemical / physical recycling of waste polyester (usually at high temperature), resulting in unwanted side reactions and impurities. Secondly, the incineration of polymer materials containing flame retardants will aggravate the release of toxic and harmful gases, especially halogen-containing flame retardants, which will release hydrogen halides and dioxins when burned, which seriously endangers health and the ecological environment. Therefore, how to prepare more environmentally friendly and recyclable multifunctional flame-retardant and anti-melting droplet polyester is of great significance to ensure life safety and resource recycling. Summary of the invention

[0005] The purpose of the present invention is to provide a multifunctional flame retardant and anti-melt dripping copolyester in view of the problems existing in the prior art.

[0006] Another object of the present invention is to provide a method for preparing the multifunctional flame retardant and anti-drip copolyester.

[0007] Another object of the present invention is to provide the application of the multifunctional flame retardant and anti-drip copolyester.

[0008] The multifunctional flame retardant and anti-melting droplet copolyester provided by the present invention is characterized in that the copolyester is composed of the following structural units represented by Ⅰ, Ⅱ, Ⅲ or Ⅰ, Ⅱ, Ⅲ, IV:

[0009]

[0010] In the formula, R1 represents an arylene group or a C2-C 16 Alkylene;

[0011]

[0012] In the formula, R2 represents an arylene group or a C2~C 16 Alkylene;

[0013]

[0014]

[0015] In the formula, R3 and R4 are carbonyl, O atom or a is an integer of 2 to 12, R3 and R4 are the same or different; X1, X2, X3, and X4 are H atoms, methyl groups, C2 to C 16 any one of alkyl, cyano, hydroxyl, hydroxyethyl, hydroxypropyl, hydroxybutyl, methoxyethyl, methoxy, cyclohexyl, benzyl or phenyl; X1, X2, X3, X4 may be the same or different; X5, X6, X7, X8 are methyl, C2-C 16 any one of alkyl, hydroxyethyl, hydroxypropyl, hydroxybutyl, methoxyethyl, methoxy, cyclohexyl, benzyl or phenyl, X5, X6, X7, X8 may be the same or different;

[0016]

[0017] In the formula, R5 and R6 are carbonyl, O atom or a is an integer of 2 to 12, R5 and R6 are the same or different; R7 is C1 to C 12 R8 is a C1-C8 alkylene or arylene group; Y1 is an O atom or an S atom; M is a metal atom selected from the group consisting of Li, Na, K, Mg, Cu, Ca, Mn, Co, Ni, Ba, Fe, Cs, Ag and Zn; and n is an integer of 1 to 3; X9, X 10 H atoms, methyl groups, C2~C 16 any one of alkyl, cyano, hydroxy, hydroxyethyl, hydroxypropyl, hydroxybutyl, methoxyethyl, methoxy, cyclohexyl, benzyl or phenyl, X9, X 10 Can be the same or different.

[0018] Among them, when the structural unit [III] is a structure of formula AW, the number of structural units of [III] is 0.1 to 99% of the number of structural units of [I], and the number of structural units of [IV] is 0.1 to 99% of the number of structural units of [I]; when the structural unit [III] is a structure of formula X, the number of structural units of [III] is 0.1 to 0.99% of the number of structural units of [I], and the number of structural units of [IV] is 0.1 to 99% of the number of structural units of [I].

[0019] The characteristic viscosity [η] of the above-mentioned multifunctional flame-retardant and anti-melt droplet copolyester is 0.20~2.00dL / g; the limiting oxygen index is 23~55.0%; the vertical burning grade is V-2~V-0; the shielding rate for 400nm~320nm ultraviolet rays is 1~100%; the antibacterial rate against Staphylococcus aureus is 1~99%; and the tensile strength is 50~110MPa.

[0020] In the above-mentioned multifunctional flame-retardant and anti-drip copolyester, when [III] is a structure of formula AW, the number of structural units of [III] in the copolyester is preferably 0.1 to 40% of the number of structural units of [I], and the number of structural units of [IV] is preferably 0.1 to 40% of the number of structural units of [I]; when [III] is a structure of formula X, the number of structural units of [III] in the copolyester is preferably 0.1 to 0.99% of the number of structural units of [I], and the number of structural units of [IV] is preferably 0.1 to 40% of the number of structural units of [I].

[0021] The characteristic viscosity [η] of the above-mentioned multifunctional flame-retardant and anti-melt droplet copolyester is 0.30~1.80dL / g; the limiting oxygen index is 24.0~45.0%; the vertical burning grade is V-2~V-0; the shielding rate for 400nm~320nm ultraviolet rays is 5~100%; the antibacterial rate against Staphylococcus aureus is 5~99%; and the tensile strength is 55~100MPa.

[0022] The method for preparing the above copolyester provided by the present invention comprises: preparing polyester monomers of dibasic acid or dibasic acid ester and diol and catalyst according to conventional proportions, esterifying by conventional direct esterification method or ester exchange method, and then carrying out polycondensation reaction to prepare the polyester, characterized in that: before the esterification reaction or before the polycondensation after the esterification reaction, 0.1 to 99% of AW monomer in the structural unit [III] is added to the reaction system based on the molar number of dibasic acid or dibasic acid ester in the polyester monomer, or 0.1 to 99% of AW monomer in the structural unit [III] is added to the reaction system based on the molar number of dibasic acid or dibasic acid ester in the polyester monomer. 0.1 to 99% of AW monomer in structural unit [III] and 0.1 to 99% of monomer in structural unit [IV]; or before the esterification reaction or before the polycondensation after the esterification reaction, 0.1 to 0.99% of X monomer in structural unit [III] is added to the reaction system based on the molar number of the dibasic acid or dibasic acid ester in the polyester monomer, or 0.1 to 0.99% of X monomer in structural unit [III] and 0.1 to 99% of monomer in structural unit [IV] are added to the reaction system based on the molar number of the dibasic acid or dibasic acid ester in the polyester monomer.

[0023] In the above preparation method, it is preferred to add 0.1 to 40% of the AW monomer of the structural unit [III] based on the molar number of the dibasic acid or dibasic acid ester in the polyester monomer, or to add 0.1 to 40% of the AW monomer of the structural unit [III] and 0.1 to 40% of the monomer of the structural unit [IV] based on the molar number of the dibasic acid or dibasic acid ester in the polyester monomer; or it is preferred to add 0.1 to 0.99% of the X monomer of the structural unit [III] based on the molar number of the dibasic acid or dibasic acid ester in the polyester monomer, or to add 0.1 to 0.99% of the X monomer of the structural unit [III] and 0.1 to 40% of the monomer derived from the structural unit [IV] based on the molar number of the dibasic acid or dibasic acid ester in the polyester monomer.

[0024] The monomer of the structural unit [III] used in the above preparation method is at least one of the following general structural formulas A'-X':

[0025]

[0026]

[0027] In the formula, Z1 and Z2 are carboxyl, ester, hydroxyl or a is an integer of 2 to 12, Z1 and Z2 are the same or different; X1, X2, X3, and X4 are H atoms, methyl groups, C2 to C 16 any one of alkyl, cyano, hydroxyl, hydroxyethyl, hydroxypropyl, hydroxybutyl, methoxyethyl, methoxy, cyclohexyl, benzyl or phenyl; X1, X2, X3, X4 may be the same or different; X5, X6, X7, X8 are methyl, C2-C 16 any one of alkyl, hydroxyethyl, hydroxypropyl, hydroxybutyl, methoxyethyl, methoxy, cyclohexyl, benzyl or phenyl, X5, X6, X7, X8 may be the same or different.

[0028] The monomer of the structural unit [IV] used in the above preparation method is at least one of the following structural formulas A1'-D1':

[0029]

[0030] In the formula, Z1 and Z2 are carboxyl, ester, hydroxyl or a is an integer of 2 to 12, Z1 and Z2 are the same or different; Z3 is a C2 to C8 alkylene group; R7 is a C1 to C 12 R8 is a C1-C8 alkylene or arylene group; Y1 is an O atom or an S atom; M is a metal atom selected from the group consisting of Li, Na, K, Mg, Cu, Ca, Mn, Co, Ni, Ba, Fe, Cs, Ag and Zn, and n is an integer of 1 to 3; X9, X 10 H atom, methyl, C2~C 16 any one of alkyl, cyano, hydroxy, hydroxyethyl, hydroxypropyl, hydroxybutyl, methoxyethyl, methoxy, cyclohexyl, benzyl or phenyl, X9, X 10 Can be the same or different.

[0031] The ester group in the monomers of the above structural units [III] and [IV] is a methyl ester group or an ethyl ester group after esterification with a monohydric alcohol, or is any one of an ethylene glycol ester group, a propylene glycol ester group, a butylene glycol ester group, a pentanediol ester group, a glycerol ester group or a pentaerythritol ester group after esterification with a polyhydric alcohol.

[0032] The monomer of the structural unit [III] used in the above method can be prepared by referring to the methods disclosed in Phys.Chem.Chem.Phys.2021,23,18659, Green Chem.2020,22,3122-3131, J.Org.Chem.1994,59,1333-1343, Chem.Eur.J.2019,25,7649-7658 and other documents; the monomer derived from the structural unit [IV] used in the above method can be prepared by referring to the methods disclosed in Polymer Chemistry,2014,5,1982-1991; Polymer,2015,60,50-61 and other documents.

[0033] The process steps and conditions of the conventional direct esterification method or transesterification method adopted in the present invention are specifically as follows:

[0034] Direct esterification method: add dibasic acid, diol, catalyst, monomer derived from structural unit [III] and monomer derived from structural unit [IV] in a reaction kettle according to the ratio, pressurize and heat to 190-240°C to carry out esterification reaction for 2-5 hours; after the esterification is completed, carry out polycondensation reaction at 240-250°C under low vacuum for 0.5-2 hours, and then carry out polycondensation reaction at 250-280°C under high vacuum for 1-4 hours, press out the copolyester melt with inert gas, preferably nitrogen, and water-cool the melt to obtain the target copolyester. Among them, the high-temperature self-crosslinking flame retardant monomer and ionic monomer can be added to the reaction kettle before esterification or before polycondensation after esterification.

[0035] Transesterification method: add the esterification product of dibasic acid, diol, catalyst, monomer derived from structural unit [III] and monomer derived from structural unit [IV] in a reaction kettle according to the ratio, and carry out transesterification reaction at 180-220°C under normal pressure for 3-6 hours; after the transesterification, carry out polycondensation at 240-250°C under low vacuum for 0.5-2 hours, and then carry out polycondensation at 250-280°C under high vacuum for 1-4 hours, press out the copolyester melt with inert gas (preferably nitrogen), and water-cool the melt to obtain the target copolyester. Among them, the high-temperature self-crosslinking flame retardant monomer and ionic monomer can be added to the reaction kettle before the transesterification reaction or after the transesterification reaction and before the polycondensation.

[0036] The catalyst selected in the above preparation method is at least one of a germanium-based catalyst, a titanium-based catalyst, an antimony-based catalyst, an aluminum-based catalyst, a tin-based catalyst, etc., such as germanium dioxide, antimony acetate, antimony trioxide, ethylene glycol antimony, titanium oxide, potassium titanium oxalate, potassium hexafluorotitanate, titanate, titanium alcohol, titanium complex, tin oxide, aluminum hydroxide, aluminum acetate, silicon dioxide, zinc acetate, manganese acetate or magnesium acetate, etc.

[0037] The present invention provides an application of the above copolyester, which is used in the fields of fibers, non-woven fabrics, engineering plastics, membrane materials, container materials, self-repairing materials, shape memory materials or 3D printing materials, or as a functional additive for the modification of polymer materials.

[0038] Compared with the prior art, the present invention has the following advantages:

[0039] 1. Since the structural unit [III] in the flame retardant and anti-melting droplet copolyester provided by the present invention is stable during the polymerization process and processing and will not undergo carbonization, these structural units can quickly promote the high-temperature carbonization reaction of the polyester at a higher temperature or during combustion. The occurrence of the carbonization reaction greatly increases the melt viscosity of the polyester during combustion, thereby inhibiting the generation of droplets. On the other hand, the stable and dense carbon layer formed by the carbonization reaction can play a role in heat insulation and oxygen isolation, thereby giving the copolyester excellent flame retardant and anti-melting droplet properties.

[0040] 2. Since the flame retardant and anti-dripping copolyester provided by the present invention contains both the structural unit [III] that promotes the high-temperature carbonization of polyester and the structural unit [IV] that can increase the melt viscosity of polyester by "physical crosslinking" or "chemical crosslinking", it can play a synergistic flame retardant role during combustion. Compared with the copolyester containing only the structural unit [III], the copolyester containing both the structural units [III] and [IV] can show better flame retardant and anti-dripping properties at a lower total amount of monomer introduction.

[0041] 3. Since the flame-retardant and anti-melting-drip copolyester provided by the present invention has a carbonization flame-retardant effect, a stable and dense carbon layer will be formed when the copolyester burns. The carbon layer covers the surface of the copolyester as a physical barrier layer, which can more effectively inhibit the release and volatilization of smoke during combustion, and avoid the formation of a large amount of thick smoke due to incomplete combustion products produced by thermal decomposition of the polymer when a fire occurs, resulting in obstruction of vision, inconvenience for rescue and escape, and poisoning or even suffocation of personnel, posing a fatal threat to life safety.

[0042] 4. Since the flame-retardant and anti-drip copolyester provided by the present invention contains conjugated aromatic groups, ionic groups and metal ions in its structure, it can simultaneously give the copolyester good anti-ultraviolet, antibacterial, cationic dyeability and other functionalities, has good application prospects, is conducive to the development of high-performance and high-value-added differentiated polyester products, and meets the huge demand for the development of the polyester industry.

[0043] 5. Since the flame-retardant and anti-drip copolyester provided by the present invention contains conjugated aromatic groups or secondary amine groups in its structure, these conjugated aromatic groups can form π-π stacking physical interactions, and the secondary amine groups can form hydrogen bond physical interactions with the ester groups of the polyester. These physical interactions can enhance the interaction force between the molecular chains, thereby enhancing the mechanical strength of the copolyester.

[0044] 6. Since the flame-retardant and anti-drip copolyester provided by the present invention contains ionic groups that can catalyze the alcoholysis reaction of the ester group, the copolyester can undergo a self-catalytic depolymerization reaction without an external catalyst, thereby generating raw monomers such as terephthalic acid, dimethyl terephthalate or diethylene glycol terephthalate, which is beneficial to the recycling of polyester materials after the end of their service life and promotes the recycling of polymer materials.

[0045] 7. Since the flame retardant and anti-melting dripping copolyester provided by the present invention does not contain any additives that affect fiber preparation, it has good spinnability. It can not only be directly used as a copolyester for fiber, but also be used as a macromolecular compatibilizer for incompatible polymer blending systems, so that it can improve the mechanical properties of the material while also giving the material flame retardant and anti-melting dripping properties.

[0046] 8. Since the flame-retardant and anti-melt-drip copolyester provided by the present invention does not contain halogen elements in its structure, it is an environmentally friendly polymer material.

[0047] 9. Since the copolyester preparation method provided by the present invention is basically consistent with the conventional polyester synthesis method, the process is mature, the equipment is highly portable, the operation is simple, and it is easy to control and industrialize production. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 The digital photos of the copolyester prepared in Example 6 of the present invention and the pure PET prepared in Comparative Example 1 in the vertical combustion test are shown in the figure. It can be seen from the photo that PET will not extinguish itself after being ignited, and is accompanied by a large number of molten droplets, and the test grade is levelless; the copolyester prepared in the present invention will quickly extinguish itself within 10 seconds after being ignited, and no molten droplets will be generated, and the test grade is V-0, indicating that the copolyester prepared in the present invention can have excellent flame retardant and anti-molten droplet properties.

[0049] Figure 2 The heat release rate curve of the cone calorimetry test of the copolyester prepared in Example 6 of the present invention and the pure PET prepared in Comparative Example 1 is shown in FIG. The peak heat release rate (p-HRR) is an important parameter for judging the flame retardant properties of a material. The lower the value, the better the flame retardancy of the material. From the comparison of the curves in this figure, it can be seen that the p-HRR of Example 6 of the present invention is 366kW / m 2 Compared with pure PET (797kW / m 2 ) was reduced by 54%, indicating that the copolyester prepared by the present invention exhibits excellent flame retardant properties.

[0050] Figure 3The total smoke release (TSR) curve of the cone calorimeter test of the copolyester prepared in Example 6 of the present invention and the pure PET prepared in Comparative Example 1 is shown in FIG. From the comparison of the curves in this figure, it can be seen that the TSR of the copolyester of the present invention is 928 m / s. 2 / m 2 Compared with pure PET (1783m 2 / m 2 ) was reduced by 48%, showing excellent smoke suppression performance.

[0051] Figure 4 This is a UV resistance test diagram of the copolyester prepared in Example 6 of the present invention and the pure PET prepared in Comparative Example 1. It can be seen from the figure that the transmittance of the pure PET film to ultraviolet light with a wavelength of 400nm is 83%, indicating that PET can only block 17% of 400nm ultraviolet light; the transmittance of the copolyester film to ultraviolet light with a wavelength of 400nm and below is 0%, indicating that the copolyester can 100% block ultraviolet light of the entire band, indicating that the copolyester film has excellent UV resistance.

[0052] Figure 5 The tensile test curves of the copolyester prepared in Example 6 of the present invention and the pure PET prepared in Comparative Example 1 are shown. The copolyester exhibits higher tensile strength than PET and has excellent mechanical properties.

[0053] Figure 6 The digital photos are of the glycolization recovery experiment of the copolyester prepared in Example 37 of the present invention and the pure PET prepared in Comparative Example 1. In the absence of an external catalyst, PET is difficult to react with ethylene glycol, and a large amount of blocky PET solids still exist after stirring and reacting at 200°C for 3 hours; while the copolyester is completely depolymerized, and a uniform and transparent solution is generated after reacting with ethylene glycol, indicating that the copolyester has an excellent self-catalytic depolymerization effect.

[0054] Figure 7 The NMR hydrogen spectra of commercially purchased BHET and the BHET monomer in the copolyester recovery experiment prepared in Example 37 of the present invention are shown in FIG. As can be seen from the figure, the peak positions of the two in the NMR are consistent and there are no impurity peaks, indicating that the BHET recovered by the self-catalytic depolymerization of the copolyester has a high purity. DETAILED DESCRIPTION

[0055] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by those having ordinary skills in the field to which the present invention belongs.

[0056] The term "diacid ester" in the present invention refers to an ester of a dibasic acid, such as dibasic acid dimethyl ester and dibasic acid diethyl ester.

[0057] The term "aryl" refers to a cyclic aromatic hydrocarbon group having 1 to 3 aromatic rings, especially a monocyclic or bicyclic group, such as phenyl or naphthyl. A bicyclic or tricyclic aryl must contain at least one fully aromatic carbon ring, but the other fused rings can be aromatic or non-aromatic and can optionally contain heteroatoms, provided that in the above cases the point of attachment should be on the aromatic carbon ring.

[0058] The term "arylene" refers to a divalent aryl group, i.e., an aryl group as defined above having two attachment points for attachment to two other groups at any available attachment point on the aryl ring, such as phenylene and naphthylene. The arylene group can also be substituted with any group suitable for substitution on the aryl group defined in the present invention.

[0059] The terms "alkyl" or "alkylene" in the present invention refer to branched and straight-chain saturated aliphatic hydrocarbon groups having a specified number of carbon atoms. For example, "C 1-8 alkyl (or alkylene)" is intended to include C1, C2, C3, C4, C5, C6, C7 and C8 alkyl (or alkylene). The alkyl (or alkylene) group can be unsubstituted, or the alkyl (or alkylene) group can be substituted, where at least one hydrogen is replaced by another chemical group.

[0060] Examples are given below and the present invention is further described in detail, but the embodiments of the present invention are not limited thereto. It is necessary to reiterate that the following examples should not be construed as limiting the scope of protection of the present invention. If those skilled in the art make some non-essential improvements and adjustments to the present invention based on the above content of the present invention, it still falls within the scope of protection of the present invention.

[0061] In addition, it is worth noting that 1) the intrinsic viscosity [η] of the flame-retardant and anti-dripping copolyester obtained in the following examples was measured at 25 °C using an Ubbelohde viscometer on a solution prepared with phenol / 1,1,2,2-tetrachloroethane (1:1, v:v) at a concentration of 5 g / L. 2) The limiting oxygen index of the copolyester was measured on a standard oxygen index test specimen of 120×6.5×3.2 mm3 in accordance with ASTM D2863-97 on an HC-2 type oxygen index instrument. The limiting oxygen index (LOI) characterizes the self-extinguishing ability of the material, and the larger the LOI value, the better the flame-retardant performance of the material. Generally, materials with an LOI greater than 26% are considered self-extinguishing materials. 3) The vertical burning test was carried out on a standard specimen of 125×12.7×3.2 mm 3 of the copolyester in accordance with the UL-94 standard using a CZF-2 type vertical burning instrument (UL-94). The test grades are non-rated, V-2 grade, V-1 grade and V-0 grade. Non-rated means that the material is extremely flammable, and the flame-retardant performance of the material is: V-2 grade < V-1 grade < V-0 grade. The cone calorimeter test was carried out on a specimen of 100×100×3 mm 3The standard sample was tested in accordance with ISO 5660-1 in a FTT cone calorimeter at 50 kW / m 2 4) The antibacterial test was carried out in accordance with QB-T 2591-2018 or GB / T 31402-2015 standards. 5) The tensile strength was measured using an INSTRON 3366 electronic universal material testing machine with a tensile rate of 5 mm / min and a sample size of 25×4×2 mm. 3 Dumbbell-shaped specimens. 6) The UV resistance test was carried out on a Cary50 UV-visible spectrophotometer, and the sample was a 0.3 mm film. The dyeing performance test used methylene blue as a cationic dye, weighed 1 g of polyester fiber sample for dyeing test, and the dye solution absorbance test was carried out by a UV-visible spectrophotometer, and the absorbance at a wavelength of 665 nm was taken as the maximum absorbance.

[0062] Example 1

[0063] 498.0g of terephthalic acid, 220.0g of ethylene glycol, 89.7g of 5-(2H-benzo[e][1,3]oxazine-3(4H)-yl)isophthalic acid and 0.3g of tetrabutyl titanate are added to a reaction kettle, nitrogen is filled to remove the air in the kettle, the kettle is pressurized to 0.1MPa, the temperature is raised to 240-250°C within 2 hours to start the esterification reaction, the pressure in the kettle is controlled to be 0.3-0.4MPa, and after maintaining for 2-6 hours, the pressure begins to decrease to normal pressure, and the esterification reaction ends; then, a low vacuum polycondensation reaction is carried out at 240°C for 0.5-2 hours, and then the temperature is raised to 250-270°C, and after a high vacuum (pressure <80Pa) polycondensation reaction for 1-4 hours, the material is discharged and water-cooled.

[0064] The intrinsic viscosity [η] of the copolyester is 0.61 dL / g; the limiting oxygen index is 28.0%; the vertical combustion grade is V-0, and no molten droplets are generated during the test; the peak heat release rate p-HRR in the cone calorimetry test is 402 kW / m 2 The total smoke release TSR is 1239m 2 / m 2 The shielding rate for 400-320nm ultraviolet rays is 99%, the antibacterial rate for Staphylococcus aureus is 45%, and the tensile strength is 66MPa.

[0065] Example 2

[0066] 582.0g of dimethyl terephthalate, 400.0g of ethylene glycol, 11.3g of 5-(1H-naphtho[1,2-e][1,3]oxazine-2(3H)-yl)dimethyl isophthalate, 0.2g of zinc acetate and 0.25g of antimony trioxide are added to a reaction kettle, and nitrogen is filled to remove the air in the kettle; the reaction is carried out at 180-220°C under normal pressure for 3-6 hours, and the ester exchange reaction is completed; thereafter, a low vacuum polycondensation reaction is carried out at 240-250°C for 0.5-2h, and then a high vacuum polycondensation reaction is carried out at 250-270°C for 1-4 hours (pressure <80Pa), the material is discharged, and water-cooled.

[0067] The intrinsic viscosity [η] of the copolyester is 0.65 dL / g; the limiting oxygen index is 25%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 670kW / m 2 , TSR is 1630m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 75%; the antibacterial rate for Staphylococcus aureus is 36%; the tensile strength is 60MPa.

[0068] Example 3

[0069] 388.0 g of dimethyl terephthalate, 194 g of dimethyl isophthalate, 400.0 g of ethylene glycol, 56.5 g of 5-(1H-naphtho[1,2-e][1,3]oxazine-2(3H)-yl)dimethyl isophthalate and 0.28 g of isopropyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions of Example 2, and then the material was discharged.

[0070] The intrinsic viscosity [η] of the copolyester is 0.60 dL / g; the limiting oxygen index is 28.0%; the vertical combustion grade is V-0, and no droplets are generated during the test; the p-HRR in the cone calorimetry test is 588 kW / m 2 , TSR is 1455m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 90%; the antibacterial rate for Staphylococcus aureus is 40%; the tensile strength is 68MPa.

[0071] Example 4

[0072] 498.0 g of terephthalic acid, 400.0 g of butanediol, 211.2 g of methyl 3-(3-cyano-4-(methoxycarbonyl)phenyl)-3,4-dihydro-2H-benzo[e][1,3]oxazine-6-carboxylate, 0.2 g of zinc acetate and 0.3 g of antimony glycolate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0073] The intrinsic viscosity [η] of the copolyester is 0.81 dL / g; the limiting oxygen index is 30%; the vertical combustion grade is V-0, and no droplets are generated during the test; the p-HRR in the cone calorimetry test is 553kW / m 2 , TSR is 1346m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 48%; the tensile strength is 78MPa.

[0074] Example 5

[0075] 415.0 g of terephthalic acid, 83.0 g of phthalic acid, 220.0 g of ethylene glycol, 46.8 g of (E)-4-(2-(1-(4-(methoxycarbonyl)phenyl)ethylene)hydrazino)benzoic acid, 0.1 g of antimony acetate and 0.2 g of titanium glycolate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0076] The intrinsic viscosity [η] of the copolyester is 0.59 dL / g; the limiting oxygen index is 27.5%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 555kW / m 2 , TSR is 1335m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 78%; the antibacterial rate for Staphylococcus aureus is 39%; the tensile strength is 80MPa.

[0077] Example 6

[0078] 498.0 g of terephthalic acid, 220.0 g of ethylene glycol, 187.2 g of (E)-4-(2-(1-(4-(methoxycarbonyl)phenyl)ethylene)hydrazino)benzoic acid and 0.25 g of tetrabutyl titanate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions of Example 1, and then the material was discharged.

[0079] The intrinsic viscosity [η] of the copolyester is 0.70 dL / g; the limiting oxygen index is 33.0%; the vertical combustion grade is V-0, and no droplets are generated during the test; the p-HRR in the cone calorimetry test is 366 kW / m 2 , TSR is 928m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 56%; the tensile strength is 90MPa.

[0080] Example 7

[0081] 582.0 g of dimethyl terephthalate, 456.0 g of propylene glycol, 0.726 g of (E)-5-(1-(2-phenylhydrazono)ethyl)benzene-1,3-diol, and 0.3 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0082] The intrinsic viscosity [η] of the copolyester is 0.20 dL / g; the limiting oxygen index is 23.0%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 753kW / m 2 , TSR is 1700m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 50%; the antibacterial rate for Staphylococcus aureus is 40%; the tensile strength is 50MPa.

[0083] Example 8

[0084] 354.0 g of succinic acid, 540.0 g of 1,4-butanediol, 212.4 g of (Z)-5-(2-(1-phenyleneethylene)hydrazino)isophthalic acid diethyl ester, 0.2 g of zinc acetate and 0.2 g of antimony glycol were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0085] The intrinsic viscosity [η] of the copolyester is 3.0 dL / g; the limiting oxygen index is 28.0%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 640kW / m 2 , TSR is 1490m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 99%; the antibacterial rate for Staphylococcus aureus is 50%; the tensile strength is 82MPa.

[0086] Example 9

[0087] 498.0 g of terephthalic acid, 220.0 g of ethylene glycol, 30.8 g of 1H-indole-2,5-dicarboxylic acid and 0.3 g of antimony glycol were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0088] The intrinsic viscosity [η] of the copolyester is 0.70 dL / g; the limiting oxygen index is 26.0%; the vertical burning grade is V-0, and there is no droplet in the test; the p-HRR in the cone calorimetry test is 568 kW / m 2 , TSR is 1222m 2 / m 2; The shielding rate for 400-320nm ultraviolet rays is 60%; the antibacterial rate for Staphylococcus aureus is 43%; the tensile strength is 76MPa.

[0089] Example 10

[0090] 498.0 g of terephthalic acid, 220.0 g of ethylene glycol, 92.3 g of 1H-indole-2,5-dicarboxylic acid and 0.3 g of tetrabutyl titanate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0091] The intrinsic viscosity [η] of the copolyester is 0.75 dL / g; the limiting oxygen index is 29.5%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 507kW / m 2 , TSR is 1010m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 70%; the antibacterial rate for Staphylococcus aureus is 53%; the tensile strength is 78MPa.

[0092] Embodiment 11

[0093] 415.0 g of terephthalic acid, 53.0 g of isophthalic acid, 153.8 g of 1H-indole-2,5-dicarboxylic acid and 0.27 g of antimony glycolate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0094] The intrinsic viscosity [η] of the copolyester is 0.64 dL / g; the limiting oxygen index is 31.0%; the vertical combustion grade is V-0, and no droplets are generated during the test; the p-HRR in the cone calorimetry test is 455 kW / m 2 , TSR is 979m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 85%; the antibacterial rate for Staphylococcus aureus is 60%; the tensile strength is 80MPa.

[0095] Example 12

[0096] 498.0 g of terephthalic acid, 400.0 g of 1,4-butanediol, 52.0 g of neopentyl glycol, 235.8 g of 5,6-bis(2-hydroxyethoxy)-1H-indole-3-carbonitrile, 0.15 g of zinc acetate, 0.3 g of aluminum oxide and 0.1 g of antimony trioxide were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions of Example 1, and then the material was discharged.

[0097] The intrinsic viscosity [η] of the copolyester is 2.0 dL / g; the limiting oxygen index is 32.0%; the vertical combustion grade is V-0, and no droplets are generated during the test; the p-HRR in the cone calorimetry test is 389 kW / m 2 , TSR is 1023m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 40%; the tensile strength is 90MPa.

[0098] Example 13

[0099] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 0.468 g of furan-2,5-dicarboxylic acid and 0.2 g of tetrabutyl titanate were added to a reaction kettle, and after ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, the material was discharged.

[0100] The intrinsic viscosity [η] of the copolyester is 0.65 dL / g; the limiting oxygen index is 23.0%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 755kW / m 2 , TSR is 1706m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 40%; the antibacterial rate for Staphylococcus aureus is 42%; the tensile strength is 80MPa.

[0101] Embodiment 14

[0102] 498.0 g of terephthalic acid, 220.0 g of ethylene glycol, 2.34 g of furan-2,5-dicarboxylic acid and 0.25 g of tetraethyl titanate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0103] The intrinsic viscosity [η] of the copolyester is 0.63 dL / g; the limiting oxygen index is 23.5%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 736kW / m 2 , TSR is 1688m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 45%; the antibacterial rate for Staphylococcus aureus is 48%; the tensile strength is 83MPa.

[0104] Embodiment 15

[0105] 498.0 g of terephthalic acid, 220.0 g of ethylene glycol, 4.633 g of furan-2,5-dicarboxylic acid and 0.3 g of potassium titanium oxalate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions of Example 1, and then the material was discharged.

[0106] The intrinsic viscosity [η] of the copolyester is 0.66 dL / g; the limiting oxygen index is 24.0%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 720kW / m 2 , TSR is 1670m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 51%; the antibacterial rate for Staphylococcus aureus is 55%; the tensile strength is 85MPa.

[0107] Example 16

[0108] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 5.16 g of thiophene-2,5-dicarboxylic acid, 0.5 g of zinc acetate and 0.5 g of antimony glycolate were added to a reaction kettle, and after ester exchange and polycondensation reactions were carried out according to the steps and conditions of Example 2, the material was discharged.

[0109] The intrinsic viscosity [η] of the copolyester is 0.70 dL / g; the limiting oxygen index is 23.0%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 735kW / m 2 , TSR is 1735m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 35%; the antibacterial rate for Staphylococcus aureus is 41%; the tensile strength is 88MPa.

[0110] Embodiment 17

[0111] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 15.48 g of thiophene-2,5-dicarboxylic acid, and 0.24 g of tetraisopropyl titanate were added to a reaction kettle, and after ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, the material was discharged.

[0112] The intrinsic viscosity [η] of the copolyester is 0.71 dL / g; the limiting oxygen index is 23.6%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 718kW / m 2 , TSR is 1718m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 37%; the antibacterial rate for Staphylococcus aureus is 45%; the tensile strength is 89MPa.

[0113] Embodiment 18

[0114] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 25.8 g of thiophene-2,5-dicarboxylic acid and 0.3 g of antimony glycol were added to a reaction kettle, and after ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, the material was discharged.

[0115] The intrinsic viscosity [η] of the copolyester is 0.65 dL / g; the limiting oxygen index is 24.0%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 698kW / m 2 , TSR is 1694m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 40%; the antibacterial rate for Staphylococcus aureus is 48%; the tensile strength is 90MPa.

[0116] Embodiment 19

[0117] 582.0 g of dimethyl terephthalate, 550.0 g of 1,4-butanediol, 154.8 g of thiophene-2,5-dicarboxylic acid, and 0.24 g of tetrabutyl titanate were added to a reaction kettle, and after ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, the material was discharged.

[0118] The intrinsic viscosity [η] of the copolyester is 1.00 dL / g; the limiting oxygen index is 27.0%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 718kW / m 2 , TSR is 1706m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 55%; the antibacterial rate for Staphylococcus aureus is 56%; the tensile strength is 95MPa.

[0119] Embodiment 20

[0120] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 37.2 g of 3-phenylthiophene-2,5-dicarboxylic acid, 0.2 g of zinc acetate and 0.2 g of germanium oxide were added to a reaction kettle, and after ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, the material was discharged.

[0121] The intrinsic viscosity [η] of the copolyester is 0.70 dL / g; the limiting oxygen index is 25.0%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 688kW / m 2 , TSR is 1647m 2 / m2 ; The shielding rate for 400-320nm ultraviolet rays is 60%; the antibacterial rate for Staphylococcus aureus is 45%; the tensile strength is 78MPa.

[0122] Embodiment 21

[0123] 388.0 g of dimethyl terephthalate, 118.0 g of succinic acid, 400.0 g of ethylene glycol, 121.2 g of 3-methoxythiophene-2,5-dicarboxylic acid, and 0.15 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0124] The intrinsic viscosity [η] of the copolyester is 0.90 dL / g; the limiting oxygen index is 26.0%; the vertical combustion grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 694kW / m 2 , TSR is 1683m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 65%; the antibacterial rate for Staphylococcus aureus is 46%; the tensile strength is 75MPa.

[0125] Embodiment 22

[0126] 498.0 g of terephthalic acid, 220.0 g of ethylene glycol, 118.2 g of 3-cyanothiophene-2,5-dicarboxylic acid and 0.3 g of titanium dioxide were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions of Example 1, and then the material was discharged.

[0127] The intrinsic viscosity [η] of the copolyester is 0.62 dL / g; the limiting oxygen index is 29.0%; the vertical combustion grade is V-0, and no droplets are generated during the test; the p-HRR in the cone calorimetry test is 554 kW / m 2 , TSR is 1465m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 56%; the antibacterial rate for Staphylococcus aureus is 42%; the tensile strength is 70MPa.

[0128] Embodiment 23

[0129] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 140.4 g of 1H-imidazole-4,5-dicarboxylic acid and 0.3 g of tetrabutyl titanate were added to a reaction kettle, and after ester exchange and polycondensation reactions were carried out according to the steps and conditions of Example 2, the material was discharged.

[0130] The intrinsic viscosity [η] of the copolyester is 0.62 dL / g; the limiting oxygen index is 30.2%; the vertical combustion grade is V-0, and no droplets are generated during the test; the p-HRR in the cone calorimetry test is 566 kW / m 2 , TSR is 1345m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 50%; the antibacterial rate for Staphylococcus aureus is 58%; the tensile strength is 100MPa.

[0131] Embodiment 24

[0132] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 46.8 g of 1H-imidazole-4,5-dicarboxylic acid, 0.2 g of manganese acetate and 0.2 g of tetraisopropyl titanate were added to a reaction kettle, and after ester exchange and polycondensation reactions were carried out according to the steps and conditions of Example 2, the material was discharged.

[0133] The intrinsic viscosity [η] of the copolyester is 0.66 dL / g; the limiting oxygen index is 25.5%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 679kW / m 2 , TSR is 1564m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 39%; the antibacterial rate for Staphylococcus aureus is 43%; the tensile strength is 85MPa.

[0134] Embodiment 25

[0135] 498.0 g of terephthalic acid, 320.0 g of 1,3-propylene glycol, 93.6 g of 3,5-pyrazoledicarboxylic acid and 0.3 g of tetrabutyl titanate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0136] The intrinsic viscosity [η] of the copolyester is 0.90 dL / g; the limiting oxygen index is 29.0%; the vertical combustion grade is V-0, and no droplets are generated during the test; the p-HRR in the cone calorimetry test is 542 kW / m 2 , TSR is 1236m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 60%; the antibacterial rate for Staphylococcus aureus is 62%; the tensile strength is 75MPa.

[0137] Embodiment 26

[0138] 498.0 g of terephthalic acid, 400.0 g of 1,4-butanediol, 103.2 g of 4-hydroxy-1H-pyrazole-3,5-dicarboxylic acid and 0.3 g of antimony trioxide were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0139] The intrinsic viscosity [η] of the copolyester is 0.99 dL / g; the limiting oxygen index is 30.0%; the vertical combustion grade is V-0, and no droplets are generated during the test; the p-HRR in the cone calorimetry test is 499 kW / m 2 , TSR is 1143m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 80%; the antibacterial rate for Staphylococcus aureus is 44%; the tensile strength is 85MPa.

[0140] Embodiment 27

[0141] 498.0 g of terephthalic acid, 220.0 g of ethylene glycol, 123.6 g of 1-butyl-3-methyl-1H-imidazole 3,5-bis(methoxycarbonyl)benzenesulfonate, and 0.25 g of tetrabutyl titanate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0142] The intrinsic viscosity [η] of the copolyester is 0.61 dL / g; the limiting oxygen index is 28.0%; the vertical combustion grade is V-0, the molten drop phenomenon is significantly reduced in the test, and the molten drop does not ignite the absorbent cotton; the p-HRR in the cone calorimetry test is 648kW / m 2 , TSR is 1422m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 46%; the antibacterial rate for Staphylococcus aureus is 64%; the tensile strength is 70MPa; in the fiber dyeing experiment, the exhaustion rate is 99%.

[0143] Self-catalytic recovery experiment: Copolyester and ethylene glycol were mixed in a mass ratio of 1:10, stirred and reacted at 190°C for 3 hours, and the copolyester was completely depolymerized to form a uniform solution, and the copolyester degradation rate was 100%; when the solution was cooled to room temperature, a large amount of diethylene glycol terephthalate (BHET) solid precipitated, and the BHET recovery rate was 80%.

[0144] Embodiment 28

[0145] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 185.4 g of 1-butyl-3-methyl-1H-imidazole 3,5-bis(methoxycarbonyl)benzenesulfonate, 0.2 g of cobalt acetate and 0.25 g of titanium tartrate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0146] The intrinsic viscosity [η] of the copolyester is 0.63 dL / g; the limiting oxygen index is 29.0%; the vertical combustion grade is V-0, the molten drop phenomenon is significantly reduced in the test, and the molten drop does not ignite the absorbent cotton; the p-HRR in the cone calorimetry test is 598kW / m 2 , TSR is 1365m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 55%; the antibacterial rate for Staphylococcus aureus is 72%; the tensile strength is 75MPa; in the fiber dyeing experiment, the exhaustion rate is 99%.

[0147] Self-catalytic recovery experiment: Copolyester and ethylene glycol were mixed in a mass ratio of 1:10, stirred and reacted at 190°C for 2 hours, and the copolyester was completely depolymerized to form a uniform solution, and the copolyester degradation rate was 100%; when the solution was cooled to room temperature, a large amount of diethylene glycol terephthalate (BHET) solid precipitated, and the BHET recovery rate was 85%.

[0148] Embodiment 29

[0149] 498.0 g of terephthalic acid, 400.0 g of 1,4-butanediol, 370.8 g of (1-butyl-3-methyl-imidazole) 3,5-bis(methoxycarbonyl)benzenesulfonate, and 0.25 g of tetrabutyl titanate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0150] The intrinsic viscosity [η] of the copolyester is 1.20 dL / g; the limiting oxygen index is 31.0%; the vertical combustion grade is V-0, the molten drop phenomenon is significantly reduced in the test, and the molten drop does not ignite the absorbent cotton; the p-HRR in the cone calorimetry test is 463kW / m 2 , TSR is 1154m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 60%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 74MPa; in the fiber dyeing experiment, the exhaustion rate is 99%.

[0151] Self-catalytic recovery experiment: Copolyester and ethylene glycol were mixed in a mass ratio of 1:10, stirred and reacted at 180°C for 2 hours, and the copolyester was completely depolymerized to form a uniform solution, and the copolyester degradation rate was 100%; when the solution was cooled to room temperature, a large amount of diethylene glycol terephthalate (BHET) solid precipitated, and the BHET recovery rate was 86%.

[0152] Embodiment 30

[0153] 354.0 g of succinic acid, 450.0 g of 1,4-butanediol, 638.4 g of (2,3-dimethyl-1-octyl-benzimidazole) 3,5-bis(methoxycarbonyl)benzenesulfonate, and 0.3 g of tetrabutyl titanate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0154] The intrinsic viscosity [η] of the copolyester is 2.00 dL / g; the limiting oxygen index is 30.0%; the vertical combustion grade is V-0, the molten drop phenomenon is significantly reduced in the test, and the molten drop does not ignite the absorbent cotton; the p-HRR in the cone calorimetry test is 584kW / m 2 , TSR is 1326m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 80%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 86MPa; in the fiber dyeing experiment, the exhaustion rate is 99%.

[0155] Embodiment 31

[0156] 498.0 g of terephthalic acid, 220.0 g of ethylene glycol, 241.2 g of tetrabutylphosphonium-3,5-bis(2-hydroxyethoxy)benzenesulfonate, 0.2 g of antimony glycol and 0.1 g of titanium dioxide were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0157] The intrinsic viscosity [η] of the copolyester is 0.65 dL / g; the limiting oxygen index is 29.0%; the vertical combustion grade is V-0, the molten drop phenomenon is significantly reduced in the test, and the molten drop does not ignite the absorbent cotton; the p-HRR in the cone calorimetry test is 638kW / m 2 , TSR is 1566m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 50%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 78MPa.

[0158] Embodiment 32

[0159] 582.0 g of dimethyl terephthalate, 450.0 g of 1,3-butanediol, 378 g of tributyl(ethyl)phosphine-3,5-dihydroxybenzenesulfonate, and 0.2 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0160] The intrinsic viscosity [η] of the copolyester is 0.90 dL / g; the limiting oxygen index is 30.0%; the vertical combustion grade is V-0, the molten drop phenomenon is significantly reduced in the test, and the molten drop does not ignite the absorbent cotton; the p-HRR in the cone calorimetry test is 587kW / m 2 , TSR is 1452m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 55%; the antibacterial rate for Staphylococcus aureus is 90%; the tensile strength is 70MPa.

[0161] Embodiment 33

[0162] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 567.6 g of tributyl (methyl) ammonium-3,5-bis (methoxycarbonyl) benzene sulfonate, and 0.35 g of tetrabutyl titanate were added to a reaction kettle, and after ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, the material was discharged.

[0163] The intrinsic viscosity [η] of the copolyester is 1.80 dL / g; the limiting oxygen index is 45.0%; the vertical combustion grade is V-0, and no droplets are generated in the test; the p-HRR in the cone calorimetry test is 255 kW / m 2 , TSR is 689m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 100MPa; in the fiber dyeing experiment, the exhaustion rate is 99%.

[0164] Embodiment 34

[0165] 582.0 g of dimethyl terephthalate, 400.0 g of 1,4-butanediol, 1119.7 g of 3,5-bis(methoxycarbonyl)benzenesulfonic acid choline salt, and 0.35 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0166] The intrinsic viscosity [η] of the copolyester is 2.00 dL / g; the limiting oxygen index is 55.0%; the vertical combustion grade is V-0, and no droplets are generated in the test; the p-HRR in the cone calorimetry test is 311 kW / m 2 , TSR is 764m 2 / m2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 110MPa; in the fiber dyeing experiment, the exhaustion rate is 99%.

[0167] Embodiment 35

[0168] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 188.6 g of N-methoxyethyl-N-methyldiethylammonium-3,5-bis(methoxycarbonyl)benzenesulfonate, 0.3 g of zinc acetate and 0.5 g of antimony glycol were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0169] The intrinsic viscosity [η] of the copolyester is 0.71 dL / g; the limiting oxygen index is 31.0%; the vertical combustion grade is V-0, and no droplets are generated in the test; the p-HRR in the cone calorimetry test is 503kW / m 2 , TSR is 1231m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 80%; the antibacterial rate for Staphylococcus aureus is 95%; the tensile strength is 95MPa; in the fiber dyeing experiment, the exhaustion rate is 96%.

[0170] Embodiment 36

[0171] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 61.95 g of 3,4,6,7,8,9-hexahydro-2H-pyrimido[1,2-a]pyrimidin-1-ium-3,5-bis(methoxycarbonyl)benzenesulfonate, 0.3 g of zinc acetate and 0.35 g of antimony oxide were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0172] The intrinsic viscosity [η] of the copolyester is 0.68 dL / g; the limiting oxygen index is 26.0%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced; the p-HRR in the cone calorimetry test is 617 kW / m 2 , TSR is 1405m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 85%, and the antibacterial rate for Escherichia coli is 74%; the tensile strength is 80MPa; in the fiber dyeing experiment, the exhaustion rate is 90%.

[0173] Self-catalytic recovery experiment: Copolyester and ethylene glycol were mixed at a mass ratio of 1:6, stirred and reacted at 200℃ for 3h, the copolyester was completely depolymerized to form a uniform solution, and the copolyester degradation rate was 100%; when the solution was cooled to room temperature, a large amount of diethylene glycol terephthalate (BHET) solid precipitated, and the BHET recovery rate was 65%. Alternatively, copolyester and methanol were mixed at a mass ratio of 1:10, reacted at 150℃ in a hydrothermal reactor for 10h, the copolyester degradation rate was 100%; when the solution was cooled to room temperature, a large amount of dimethyl terephthalate (DMT) solid precipitated, and the DMT recovery rate was 60%.

[0174] Embodiment 37

[0175] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 123.9 g of 3,4,6,7,8,9-hexahydro-2H-pyrimido[1,2-a]pyrimidin-1-ium-3,5-bis(methoxycarbonyl)benzenesulfonate, 0.3 g of zinc acetate and 0.35 g of antimony oxide were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0176] The intrinsic viscosity [η] of the copolyester is 0.75 dL / g; the limiting oxygen index is 28.0%; the vertical burning grade is V-2, and the droplet phenomenon is significantly reduced in the test; the p-HRR in the cone calorimetry test is 564kW / m 2 , TSR is 1233m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%, and the antibacterial rate for Escherichia coli is 99%; the tensile strength is 85MPa; in the fiber dyeing experiment, the exhaustion rate is 99%.

[0177] Self-catalytic recovery experiment: Copolyester and ethylene glycol were mixed at a mass ratio of 1:6, stirred and reacted at 200℃ for 3h, the copolyester was completely depolymerized to form a uniform solution, and the copolyester degradation rate was 100%; when the solution was cooled to room temperature, a large amount of diethylene glycol terephthalate (BHET) solid precipitated, and the BHET recovery rate was 78%. Alternatively, copolyester and methanol were mixed at a mass ratio of 1:10, reacted at 150℃ in a hydrothermal reactor for 8h, the copolyester degradation rate was 100%; when the solution was cooled to room temperature, a large amount of dimethyl terephthalate (DMT) solid precipitated, and the DMT recovery rate was 81%.

[0178] Embodiment 38

[0179] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 247.8 g of 3,4,6,7,8,9-hexahydro-2H-pyrimido[1,2-a]pyrimidin-1-ium-3,5-bis(methoxycarbonyl)benzenesulfonate, 0.3 g of zinc acetate and 0.35 g of antimony oxide were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0180] The intrinsic viscosity [η] of the copolyester is 0.70L / g; the limiting oxygen index is 32%; the vertical combustion rating is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 455kW / m 2 , TSR is 987m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%, and the antibacterial rate for Escherichia coli is 99%; the tensile strength is 90MPa; in the fiber dyeing experiment, the exhaustion rate is 99%.

[0181] Self-catalytic recovery experiment: Copolyester and ethylene glycol were mixed at a mass ratio of 1:6, stirred and reacted at 190℃ for 2h, the copolyester was completely depolymerized to form a uniform solution, and the copolyester degradation rate was 100%; when the solution was cooled to room temperature, a large amount of diethylene glycol terephthalate (BHET) solid precipitated, and the BHET recovery rate was 85%. Alternatively, copolyester and methanol were mixed at a mass ratio of 1:10, reacted at 150℃ in a hydrothermal reactor for 5h, the copolyester degradation rate was 100%; when the solution was cooled to room temperature, a large amount of dimethyl terephthalate (DMT) solid precipitated, and the DMT recovery rate was 88%.

[0182] Embodiment 39

[0183] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 837 g of N-octylpyridine-3,5-bis(methoxycarbonyl)benzenesulfonate, and 0.4 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0184] The intrinsic viscosity [η] of the copolyester is 0.85L / g; the limiting oxygen index is 48.5%; the vertical combustion rating is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 231kW / m 2 , TSR is 543m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 75MPa; in the fiber dyeing experiment, the exhaustion rate is 99%.

[0185] Self-catalytic recovery experiment: Copolyester and ethylene glycol were mixed at a mass ratio of 1:5, stirred and reacted at 180℃ for 2h, the copolyester was completely depolymerized to form a uniform solution, and the copolyester degradation rate was 100%; when the solution was cooled to room temperature, a large amount of diethylene glycol terephthalate (BHET) solid precipitated, and the BHET recovery rate was 85%. Alternatively, copolyester and methanol were mixed at a mass ratio of 1:10, reacted at 130℃ in a hydrothermal reactor for 5h, the copolyester degradation rate was 100%; when the solution was cooled to room temperature, a large amount of dimethyl terephthalate (DMT) solid precipitated, and the DMT recovery rate was 86%.

[0186] Embodiment 40

[0187] 354.0 g of succinic acid, 540.0 g of 1,4-butanediol, 1341.9 g of N-hexylpyridine-3,5-bis(4-hydroxybutoxy)benzenesulfonate, and 0.5 g of tetrabutyl titanate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0188] The intrinsic viscosity [η] of the copolyester is 1.9 dL / g; the limiting oxygen index is 46.5%; the vertical combustion grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 345kW / m 2 , TSR is 678m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 72MPa.

[0189] Embodiment 41

[0190] 498.0 g of terephthalic acid, 400.0 g of 1,3-propylene glycol, 441.9 g of 2-butylisoquinolin-2-ium-3,5-bis(3-hydroxypropoxy)benzenesulfonate, and 0.3 g of tetrabutyl titanate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0191] The intrinsic viscosity [η] of the copolyester is 1.50 dL / g; the limiting oxygen index is 32.5%; the vertical combustion grade is V-0, and no droplets are generated during the test; the p-HRR in the cone calorimetry test is 568 kW / m 2 , TSR is 987m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 80MPa.

[0192] Embodiment 42

[0193] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 222 g of 5-(methoxycarbonyl)-1,3-dimethyl-1H-imidazol-3-ium-4-(methoxycarbonyl)benzenesulfonate, and 0.4 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0194] The intrinsic viscosity [η] of the copolyester is 0.69L / g; the limiting oxygen index is 31.6%; the vertical combustion rating is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 543kW / m 2 , TSR is 1036m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 80%; the antibacterial rate for Staphylococcus aureus is 85%; the tensile strength is 76MPa; in the fiber dyeing experiment, the exhaustion rate is 99%.

[0195] Embodiment 43

[0196] 498.0 g of terephthalic acid, 380.0 g of 1,3-propylene glycol, 1185 g of 4-(3-hydroxypropoxy)-1-methylpyridin-1-ium-3-(3-hydroxypropoxy)benzenesulfonate, and 0.5 g of antimony ethylene glycol were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0197] The intrinsic viscosity [η] of the copolyester is 2.0 dL / g; the limiting oxygen index is 52%; the vertical combustion grade is V-0, and no droplets are generated during the test; the p-HRR in the cone calorimetry test is 322kW / m 2 , TSR is 501m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 78MPa; in the fiber dyeing experiment, the exhaustion rate is 99%.

[0198] Embodiment 44

[0199] 498.0 g of terephthalic acid, 220.0 g of ethylene glycol, 106.8 g of 4,5-dicarboxy-3-ethyl-1-methyl-1H-imidazole-benzenesulfonate, and 0.3 g of antimony glycol were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0200] The intrinsic viscosity [η] of the copolyester is 0.64 dL / g; the limiting oxygen index is 30%; the vertical burning grade is V-0, and there is no droplet in the test; the p-HRR in the cone calorimetry test is 539kW / m 2, TSR is 1345m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 80%; the antibacterial rate for Staphylococcus aureus is 75%; the tensile strength is 70MPa.

[0201] Embodiment 45

[0202] 450.0 g of terephthalic acid, 48.0 g of isophthalic acid, 400.0 g of 1,4-butanediol, 423.6 g of 3,5-dicarboxy-1-ethylpyridine-benzenesulfonate, 0.15 g of zinc acetate and 0.35 g of antimony trioxide were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions of Example 1, and then the material was discharged.

[0203] The intrinsic viscosity [η] of the copolyester is 1.8 dL / g; the limiting oxygen index is 40.0%; the vertical combustion grade is V-0, and no droplets are generated during the test; the p-HRR in the cone calorimetry test is 332 kW / m 2 , TSR is 865m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 87MPa.

[0204] Embodiment 46

[0205] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 46.8 g of (E)-4-(2-(1-(4-(methoxycarbonyl)phenyl)ethylene)hydrazine)benzoic acid, 5.16 g of thiophene-2,5-dicarboxylic acid, 61.95 g of 3,4,6,7,8,9-hexahydro-2H-pyrimido[1,2-a]pyrimidin-1-ium-3,5-bis(methoxycarbonyl)benzenesulfonate and 0.4 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0206] The intrinsic viscosity [η] of the copolyester is 0.65 dL / g; the limiting oxygen index is 31.0%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 588kW / m 2 , TSR is 1209m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%, and the antibacterial rate for Escherichia coli is 99%; the tensile strength is 96MPa; in the fiber dyeing experiment, the exhaustion rate is 95%.

[0207] Embodiment 47

[0208] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 285.2 g of 5-(1H-naphtho[1,2-e][1,3]oxazine-2(3H)-yl)dimethyl isophthalate, 153.75 g of 1H-indole-2,5-dicarboxylic acid and 0.4 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0209] The intrinsic viscosity [η] of the copolyester is 0.70 dL / g; the limiting oxygen index is 45.0%; the vertical combustion rating is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 301 kW / m 2 , TSR is 795m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 100MPa.

[0210] Embodiment 48

[0211] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 22.62 g of 5-(1H-naphtho[1,2-e][1,3]oxazine-2(3H)-yl)dimethyl isophthalate, 12.9 g of sodium 2,8-(2-hydroxyethoxy)carbonylphenanthreneoxaphosphinate and 0.35 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0212] The intrinsic viscosity [η] of the copolyester is 0.65 dL / g; the limiting oxygen index is 29.0%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 415kW / m 2 , TSR is 1042m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 99%; the antibacterial rate for Staphylococcus aureus is 75%; the tensile strength is 79MPa.

[0213] Embodiment 49

[0214] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 169.65 g of 5-(1H-naphtho[1,2-e][1,3]oxazine-2(3H)-yl)dimethyl isophthalate, 193.5 g of sodium 2,8-(2-hydroxyethoxy)carbonylphenanthreneoxaphosphinate and 0.35 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0215] The intrinsic viscosity [η] of the copolyester is 0.80 dL / g; the limiting oxygen index is 45.0%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 279kW / m 2 , TSR is 734m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 110MPa.

[0216] Embodiment 50

[0217] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 46.8 g of (E)-4-(2-(1-(4-(methoxycarbonyl)phenyl)ethylene)hydrazino)benzoic acid, 50.55 g of (3,5-bis(methoxycarbonyl)phenyl)zinc phosphonate and 0.40 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0218] The intrinsic viscosity [η] of the copolyester is 0.85 dL / g; the limiting oxygen index is 35.0%; the vertical combustion rating is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 308kW / m 2 , TSR is 955m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 100MPa.

[0219] Embodiment 51

[0220] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 46.8 g of (E)-4-(2-(1-(4-(methoxycarbonyl)phenyl)ethylene)hydrazine)benzoic acid, 40.2 g of sodium 5-sulfonate isophthalate and 0.30 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0221] The intrinsic viscosity [η] of the copolyester is 0.72 dL / g; the limiting oxygen index is 34.0%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 368kW / m 2 , TSR is 1147m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 88MPa.

[0222] Embodiment 52

[0223] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 374.4 g of (E)-4-(2-(1-(4-(methoxycarbonyl)phenyl)ethylene)hydrazine)benzoic acid, 321.6 g of sodium 5-sulfonate isophthalate and 0.30 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0224] The intrinsic viscosity [η] of the copolyester is 1.8 dL / g; the limiting oxygen index is 55.0%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 203kW / m 2 , TSR is 543m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 100MPa.

[0225] Embodiment 53

[0226] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 61.5 g of 1H-indole-2,5-dicarboxylic acid, 42 g of sodium (3-(2-hydroxyethoxy)-3-oxopropyl)(phenyl)phosphinate and 0.30 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0227] The intrinsic viscosity [η] of the copolyester is 0.76 dL / g; the limiting oxygen index is 35.0%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 367kW / m 2 , TSR is 809m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 86MPa.

[0228] Embodiment 54

[0229] 582.0 g of dimethyl terephthalate, 400.0 g of 1,4-butanediol, 51.6 g of thiophene-2,5-dicarboxylic acid, 105 g of potassium (3,5-bis(methoxycarbonyl)phenyl)phosphonate and 0.30 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0230] The intrinsic viscosity [η] of the copolyester is 1.20 dL / g; the limiting oxygen index is 30.0%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 507kW / m 2 , TSR is 1465m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 95%; the tensile strength is 86MPa.

[0231] Embodiment 55

[0232] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 51.6 g of thiophene-2,5-dicarboxylic acid, 80.4 g of sodium 5-sulfonate isophthalic acid and 0.30 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0233] The intrinsic viscosity [η] of the copolyester is 0.72 dL / g; the limiting oxygen index is 32.0%; the vertical combustion rating is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 469kW / m 2 , TSR is 1257m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 95%; the antibacterial rate for Staphylococcus aureus is 60%; the tensile strength is 80MPa.

[0234] Embodiment 56

[0235] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 49.44 g of 1-butyl-3-methyl-1H-imidazole 3,5-bis(methoxycarbonyl)benzenesulfonate, 50.25 g of (3,5-bis(methoxycarbonyl)phenyl)copper phosphite and 0.30 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0236] The intrinsic viscosity [η] of the copolyester is 0.65 dL / g; the limiting oxygen index is 31.5%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 502kW / m 2 , TSR is 1158m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 80%; the antibacterial rate for Staphylococcus aureus is 90%; the tensile strength is 86MPa.

[0237] Embodiment 57

[0238] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 61.95 g of 3,4,6,7,8,9-hexahydro-2H-pyrimido[1,2-a]pyrimidin-1-ium-3,5-bis(methoxycarbonyl)benzenesulfonate, 40.2 g of sodium 5-sulfonate isophthalic acid and 0.30 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0239] The intrinsic viscosity [η] of the copolyester is 0.66 dL / g; the limiting oxygen index is 34%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 408 kW / m 2 , TSR is 913m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%, and the antibacterial rate for Escherichia coli is 99%; the tensile strength is 95MPa.

[0240] Embodiment 58

[0241] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 46.8 g of (E)-4-(2-(1-(4-(methoxycarbonyl)phenyl)ethylene)hydrazino)benzoic acid, 47 g of 5-benzamido-1,3-dimethyl isophthalate and 0.30 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0242] The intrinsic viscosity [η] of the copolyester is 0.68 dL / g; the limiting oxygen index is 30%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 521 kW / m 2 , TSR is 1123m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 60%; the tensile strength is 105MPa.

[0243] Embodiment 59

[0244] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 61.95 g of 3,4,6,7,8,9-hexahydro-2H-pyrimido[1,2-a]pyrimidin-1-ium-3,5-bis(methoxycarbonyl)benzenesulfonate, 28.9 g of 5-(phenylsulfonylamino)isophthalic acid and 0.30 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0245] The intrinsic viscosity [η] of the copolyester is 0.72 dL / g; the limiting oxygen index is 31%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 536kW / m 2 , TSR is 1238m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%, and the antibacterial rate for Escherichia coli is 99%; the tensile strength is 84MPa.

[0246] Embodiment 60

[0247] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 61.5 g of 1H-indole-2,5-dicarboxylic acid, 105.6 g of silver 5-sulfonate isophthalic acid, 65.9 g of 5-phenylimide phenylacetylene-1,3-dibenzoic acid dimethyl ester and 0.30 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0248] The intrinsic viscosity [η] of the copolyester is 0.85 dL / g; the limiting oxygen index is 45%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 228kW / m 2 , TSR is 602m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%; the tensile strength is 90MPa.

[0249] Embodiment 61

[0250] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 25.8 g of thiophene-2,5-dicarboxylic acid, 40.2 g of sodium 5-sulfonate isophthalic acid, 47.0 g of 5-benzamido-1,3-dimethyl isophthalate and 0.30 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0251] The intrinsic viscosity [η] of the copolyester is 0.80 dL / g; the limiting oxygen index is 35%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 478kW / m 2 , TSR is 974m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 85%; the tensile strength is 85MPa.

[0252] Embodiment 62

[0253] 582.0 g of dimethyl terephthalate, 400.0 g of ethylene glycol, 46.8 g of (E)-4-(2-(1-(4-(methoxycarbonyl)phenyl)ethylidene)hydrazino)benzoic acid, 61.95 g of 3,4,6,7,8,9-hexahydro-2H-pyrimido[1,2-a]pyrimidin-1-ium-3,5-bis(methoxycarbonyl)benzenesulfonate, 50.55 g of zinc (3,5-bis(methoxycarbonyl)phenyl)phosphonate, 44.6 g of (E)-5-(benzylideneamino)benzene-1,3-dimethyl isophthalate and 0.30 g of tetrabutyl titanate were added to a reaction kettle, and ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, and then the material was discharged.

[0254] The intrinsic viscosity [η] of the copolyester is 0.75 dL / g; the limiting oxygen index is 45%; the vertical burning grade is V-0, and there is no droplet phenomenon in the test; the p-HRR in the cone calorimetry test is 236kW / m 2 , TSR is 612m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 100%; the antibacterial rate for Staphylococcus aureus is 99%, and the antibacterial rate for Escherichia coli is 99%; the tensile strength is 94MPa.

[0255] Self-catalytic recovery experiment: Copolyester and ethylene glycol were mixed at a mass ratio of 1:5, stirred and reacted at 200℃ for 2h, the copolyester was completely depolymerized to form a uniform solution, and the copolyester degradation rate was 100%; when the solution was cooled to room temperature, a large amount of diethylene glycol terephthalate (BHET) solid precipitated, and the BHET recovery rate was 85%. Alternatively, copolyester and methanol were mixed at a mass ratio of 1:8, reacted at 150℃ in a hydrothermal reactor for 5h, the copolyester degradation rate was 100%; when the solution was cooled to room temperature, a large amount of dimethyl terephthalate (DMT) solid precipitated, and the DMT recovery rate was 83%.

[0256] Comparative Example 1

[0257] 498.0 g of terephthalic acid, 220.0 g of ethylene glycol, 0.2 g of zinc acetate and 0.3 g of antimony glycolate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0258] The intrinsic viscosity [η] of the PET polyester is 0.63 dL / g; the limiting oxygen index is 22.0%; the vertical combustion level is stepless, and a large number of molten droplets are generated during the test; the p-HRR in the cone calorimetry test is 797 kW / m 2 ;TSR is 1783m 2 / m 2; The shielding rate for 400-320nm ultraviolet rays is 20%, and the shielding rate for 400nm ultraviolet rays is 17%; the antibacterial rate against Staphylococcus aureus is 20%; the tensile strength is 58MPa; in the fiber dyeing experiment, the exhaustion rate is 7%.

[0259] Recycling experiment: PET polyester and ethylene glycol were mixed at a mass ratio of 1:10, stirred and reacted at 200℃ for 3h, PET polyester was not completely depolymerized, and the degradation rate of PET polyester was 30%; a small amount of diethylene glycol terephthalate (BHET) solid precipitated when the solution was cooled to room temperature, and the recovery rate of BHET was 16%. Alternatively, copolyester and methanol were mixed at a mass ratio of 1:10, reacted at 150℃ in a hydrothermal reactor for 10h, and the degradation rate of copolyester was 10%; a very small amount of DMT precipitated when the solution was cooled to room temperature, and the recovery rate of DMT was 3%.

[0260] Comparative Example 2

[0261] 582.0 g of dimethyl terephthalate, 550.0 g of 1,4-butanediol, and 0.35 g of tetrabutyl titanate were added to a reaction kettle, and after ester exchange and polycondensation reactions were carried out according to the steps and conditions given in Example 2, the material was discharged.

[0262] The intrinsic viscosity [η] of the PBT polyester is 0.98 dL / g; the limiting oxygen index is 20.0%; the vertical combustion level is stepless, and a large number of molten droplets are generated during the test; the p-HRR in the cone calorimetry test is 997 kW / m 2 ;TSR is 2251m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 10%; the antibacterial rate for Staphylococcus aureus is 15%; the tensile strength is 50MPa.

[0263] Comparative Example 3

[0264] 582.0 g of succinic acid, 550.0 g of 1,4-butanediol and 0.50 g of tetrabutyl titanate were added to a reaction kettle, and esterification and polycondensation reactions were carried out according to the steps and conditions given in Example 1, and then the material was discharged.

[0265] The intrinsic viscosity [η] of the PBS polyester is 1.20 dL / g; the limiting oxygen index is 20.0%; the vertical combustion level is stepless, and a large number of molten droplets are generated during the test; the p-HRR in the cone calorimetry test is 1276 kW / m 2 ;TSR is 2509m 2 / m 2 ; The shielding rate for 400-320nm ultraviolet rays is 0%; the antibacterial rate for Staphylococcus aureus is 10%; the tensile strength is 31MPa.

Claims

1. A multifunctional flame retardant and anti-drip copolyester, characterized in that The copolyester is composed of the following structural units represented by Ⅰ, Ⅱ, Ⅲ or Ⅰ, Ⅱ, Ⅲ, IV: In the formula, R1 represents an arylene group or a C2-C 16 Alkylene; In the formula, R2 represents an arylene group or a C2~C 16 Alkylene; In the formula, R3 and R4 are carbonyl, O atom or a is an integer of 2 to 12, R3 and R4 are the same or different; X1, X2, X3, and X4 are H atoms, methyl groups, C2 to C 16 any one of alkyl, cyano, hydroxyl, hydroxyethyl, hydroxypropyl, hydroxybutyl, methoxyethyl, methoxy, cyclohexyl, benzyl or phenyl; X1, X2, X3, X4 may be the same or different; X5, X6, X7, X8 are methyl, C2-C 16 any one of alkyl, hydroxyethyl, hydroxypropyl, hydroxybutyl, methoxyethyl, methoxy, cyclohexyl, benzyl or phenyl, X5, X6, X7, X8 may be the same or different; In the formula, R5 and R6 are carbonyl, O atom or a is an integer of 2 to 12, R5 and R6 are the same or different; R7 is C1 to C 12 R8 is a C1-C8 alkylene or arylene group; Y1 is an O atom or an S atom; M is a metal atom selected from the group consisting of Li, Na, K, Mg, Cu, Ca, Mn, Co, Ni, Ba, Fe, Cs, Ag and Zn; and n is an integer of 1 to 3; X9, X 10 H atoms, methyl groups, C2~C 16 any one of alkyl, cyano, hydroxy, hydroxyethyl, hydroxypropyl, hydroxybutyl, methoxyethyl, methoxy, cyclohexyl, benzyl or phenyl, X9, X 10 May be the same or different; When the structural unit [III] is a structure of the formula AW, the number of structural units of [III] is 0.1 to 99% of the number of structural units of [I], and the number of structural units of [IV] is 0.1 to 99% of the number of structural units of [I]; when the structural unit [III] is a structure of the formula X, the number of structural units of [III] is 0.1 to 0.99% of the number of structural units of [I], and the number of structural units of [IV] is 0.1 to 99% of the number of structural units of [I]. The multifunctional flame retardant and anti-melting droplet copolyester has an intrinsic viscosity [η] of 0.20 to 2.00 dL / g; a limiting oxygen index of 23 to 55.0%; a vertical burning grade of V-2 to V-0; a shielding rate for 400 nm to 320 nm ultraviolet rays of 1 to 100%; an antibacterial rate for Staphylococcus aureus of 1 to 99%; and a tensile strength of 50 to 110 MPa.

2. The multifunctional flame retardant and anti-drip copolyester according to claim 1, characterized in that When [III] is a structure of formula AW, the number of structural units of [III] in the copolyester is 0.1-40% of the number of structural units of [I], and the number of structural units of [IV] is 0.1-40% of the number of structural units of [I]; when [III] is a structure of formula X, the number of structural units of [III] in the copolyester is 0.1-0.99% of the number of structural units of [I], and the number of structural units of [IV] is 0.1-40% of the number of structural units of [I], and the intrinsic viscosity [η] of the multifunctional flame-retardant and anti-melting droplet copolyester is 0.30-1.80 dL / g; the limiting oxygen index is 24.0-45.0%; the vertical burning grade is V-2-V-0; the shielding rate for 400nm-320nm ultraviolet rays is 5-100%; the antibacterial rate of Staphylococcus aureus is 5-99%; and the tensile strength is 55-100MPa.

3. A method for preparing the multifunctional flame retardant and anti-melting copolyester according to claim 1, wherein the polyester monomer of dibasic acid or dibasic acid ester and diol and a catalyst are mixed in a conventional ratio, esterified by a conventional direct esterification method or an ester exchange method, and then subjected to a polycondensation reaction to prepare the multifunctional flame retardant and anti-melting copolyester, characterized in that: Before the esterification reaction or before the polycondensation after the esterification reaction, 0.1 to 99% of the AW monomer in the structural unit [III] is added to the reaction system based on the molar number of the dibasic acid or dibasic acid ester in the polyester monomer, or 0.1 to 99% of the AW monomer in the structural unit [III] and 0.1 to 99% of the monomer in the structural unit [IV] are added to the reaction system based on the molar number of the dibasic acid or dibasic acid ester in the polyester monomer; or before the polycondensation after the esterification reaction, 0.1 to 0.99% of the X monomer in the structural unit [III] is added to the reaction system based on the molar number of the dibasic acid or dibasic acid ester in the polyester monomer, or 0.1 to 0.99% of the X monomer in the structural unit [III] and 0.1 to 99% of the monomer in the structural unit [IV] are added to the reaction system based on the molar number of the dibasic acid or dibasic acid ester in the polyester monomer.

4. The method for preparing a multifunctional flame retardant and anti-drip copolyester according to claim 3, wherein 0.1-40% of AW monomer of structural unit [III] is added based on the molar number of dibasic acid or dibasic acid ester in the polyester monomer, or 0.1-40% of AW monomer of structural unit [III] and 0.1-40% of monomer of structural unit [IV] are added based on the molar number of dibasic acid or dibasic acid ester in the polyester monomer; or 0.1-0.99% of X monomer of structural unit [III] is added based on the molar number of dibasic acid or dibasic acid ester in the polyester monomer, or 0.1-0.99% of X monomer of structural unit [III] and 0.1-40% of monomer derived from structural unit [IV] are added based on the molar number of dibasic acid or dibasic acid ester in the polyester monomer.

5. The method for preparing a multifunctional flame retardant and anti-drip copolyester according to claim 3 or 4, wherein the monomer of the structural unit [III] used in the method is at least one of the following general structural formulas A'-X': In the formula, Z1 and Z2 are carboxyl, ester, hydroxyl or a is an integer of 2 to 12, Z1 and Z2 are the same or different; X1, X2, X3, and X4 are H atoms, methyl groups, C2 to C 16 any one of alkyl, cyano, hydroxyl, hydroxyethyl, hydroxypropyl, hydroxybutyl, methoxyethyl, methoxy, cyclohexyl, benzyl or phenyl; X1, X2, X3, X4 may be the same or different; X5, X6, X7, X8 are methyl, C2-C 16 any one of alkyl, hydroxyethyl, hydroxypropyl, hydroxybutyl, methoxyethyl, methoxy, cyclohexyl, benzyl or phenyl, X5, X6, X7, X8 may be the same or different, The monomer of the structural unit [IV] used is at least one of the following general structural formulas A1'-D1': In the formula, Z1 and Z2 are carboxyl, ester, hydroxyl or a is an integer of 2 to 12, Z1 and Z2 are the same or different; Z3 is a C2 to C8 alkylene group; R7 is a C1 to C 12 R8 is a C1-C8 alkylene or arylene group; Y1 is an O atom or an S atom; M is a metal atom selected from the group consisting of Li, Na, K, Mg, Cu, Ca, Mn, Co, Ni, Ba, Fe, Cs, Ag and Zn, and n is an integer of 1 to 3; X9, X 10 H atoms, methyl groups, C2~C 16 any one of alkyl, cyano, hydroxy, hydroxyethyl, hydroxypropyl, hydroxybutyl, methoxyethyl, methoxy, cyclohexyl, benzyl or phenyl, X9, X 10 Can be the same or different.

6. The method for preparing a multifunctional flame retardant and anti-drip copolyester according to claim 5, wherein the ester group in the monomers of the structural unit [III] and the structural unit [IV] used in the method is a methyl ester group or an ethyl ester group after esterification with a monohydric alcohol, or any one of an ethylene glycol ester group, a propylene glycol ester group, a butylene glycol ester group, a pentanediol ester group, a glycerol ester group or a pentaerythritol ester group after esterification with a polyhydric alcohol.

7. The method for preparing a multifunctional flame-retardant and anti-drip copolyester according to claim 3 or 4, wherein the catalyst used in the method is at least one of a germanium-based catalyst, a titanium-based catalyst, an antimony-based catalyst, an aluminum-based catalyst, a tin-based catalyst, and the like.

8. The method for preparing a multifunctional flame-retardant and anti-drip copolyester according to claim 5, wherein the catalyst used in the method is at least one of a germanium-based catalyst, a titanium-based catalyst, an antimony-based catalyst, an aluminum-based catalyst, a tin-based catalyst, and the like.

9. An application of the multifunctional flame retardant and anti-melting copolyester according to claim 1, wherein the application is to use it in the fields of fibers, non-woven fabrics, engineering plastics, film materials, container materials, self-repairing materials, shape memory materials or 3D printing materials, or Used as a functional additive to modify polymer materials.

Citation Information

Cited By

  • Nitrogen-containing compound-based anti-ultraviolet anti-blue-light flame-retardant copolyester as well as preparation method and application thereof

    CN121378703A